2021
DOI: 10.3390/ijerph182412974
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive and Dual Cigarette and Hookah Smoking Is Associated with Adverse Perinatal Outcomes among Pregnant Women in Cairo, Egypt

Abstract: This study assessed the prevalence of prenatal smoking, factors associated with prenatal smoking, and its association with birth outcomes in a sample of pregnant women in Egypt. Pregnant women were recruited during their last trimester from antenatal clinics in Cairo from June 2015 to May 2016. Participants completed an interviewer-administered survey that assessed tobacco use and attitudes, and exhaled carbon monoxide (CO) was measured. Gestational age at delivery and offspring birth weight were collected via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A study conducted among pregnant women in Egypt reported lower mean birth weight ( p -value <.001) compared to non-smokers, however women who smoked included cigarette and waterpipe smoking, though waterpipe was more prevalent. 39 Another study based on a prospective cohort in Iran, reported the adjusted risk of low birth weight to be twice among waterpipe smokers. 40 The possible explanation could be the exposure to smoke that contains toxicants from the tobacco product itself in addition to the burning of charcoal which is required when using a waterpipe.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among pregnant women in Egypt reported lower mean birth weight ( p -value <.001) compared to non-smokers, however women who smoked included cigarette and waterpipe smoking, though waterpipe was more prevalent. 39 Another study based on a prospective cohort in Iran, reported the adjusted risk of low birth weight to be twice among waterpipe smokers. 40 The possible explanation could be the exposure to smoke that contains toxicants from the tobacco product itself in addition to the burning of charcoal which is required when using a waterpipe.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mendelian randomization revealed a causal role of four differentially methylated regions related to maternal smoking in inflammatory bowel disease or schizophrenia ( Wiklund et al, 2019 ). For waterpipe smoking, studies on the parental-offspring transmission of epigenetic effects are lacking, so its relationship to increased health risks, such as premature birth, low birthweight, and allergies observed in offsprings born to waterpipe smokers ( Waked and Salameh, 2015 , Al-Sheyab et al, 2016 , El-Shahawy et al, 2021 ), remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Women with chronic medical conditions before and during pregnancy such as hypertension, diabetes mellitus, heart disease, and renal disease, as well as women who were believed to be mentally or physically incapable of participating in the interview, as judged by the interviewer, were excluded from the sample. Full survey details have been reported elsewhere [ 32 ]. Informed consent was obtained from all participants, who provided signed consent prior to survey administration, and appropriate permissions were obtained from participating clinics.…”
Section: Methodsmentioning
confidence: 99%